Efektivitas Media Pembelajaran Pada Pendekatan Ilmiah (Scientefic Approach) Dalam Implementasi Kurikulum 2013 Pada Mata Pelajaran Ekonomi Kelas XI Di SMA Muhammadiyah 1 Surakarta - Inayah, Fatkhiyatul; , Dr. Suyatmini SE, M.Si (2015)
The purpose of this study was to describe: 1) instructional media used on Scientific approach in the implementation of Curriculum 2013 on economic subjects in class XI in SMA Muhammadiyah 1 Surakarta, 2) the effectiveness of the use of instructional media on Scientific approach in the implementation of Curriculum 2013 on economic subjects Class XI at SMA Muhammadiyah 1 Surakarta, 3) factors that are a barrier to the use of instructional media Scientific approach in the implementation of Curriculum 2013 on economic subjects in class XI SMA Muhammadiyah 1 Surakarta. The method used in this research is descriptive qualitative method. The data in this study was obtained from sources which consist of class XI economics teacher, deputy head of the curriculum and the students of class XI in SMA Muhammadiyah 1 Surakarta. Data collected by using interview, observation, and documentation. Data analysis was performed through three stages: data reduction, data presentation, and data verification. To maintain the validity of the data, carried out activities and membercheck triangulation. The results showed: 1) There are several types of media that can be used on Scientific approach in the implementation of Curriculum 2013 in SMA Muhammadiyah 1 Surakarta namely graphic or visual media such as whiteboards, images, tables, sterofom, and the karton.selain paper, media projections still or audiovisual such as a computer, or powerpoint slides and games, 2) use of instructional media on Scientific approach in the implementation of Curriculum 2013 on economic subjects in class XI SMA Muhammadiyah 1 Surakarta can be said to be effective. It can be seen from how to teach teachers to use the media in a variety of learning activities to observe, ask, gather information, process and communicate information so that students can discover and develop concepts or information obtained. Media used as much as possible to help the learning process so as to streamline the learning process, draw the attention of students and help teachers achieve the learning objectives that have been formulated, 3) Barriers learning media on Scientific approach in the implementation of the curriculum 2013 economic subjects in class XI SMA Muhammadiyah 1 Surakarta is the readiness of the human resources that include creativity, the age factor of teachers and students in learning readiness.